Education in Aqidah and Faith in the Qur'an - Robitul Abror; Farhan; Ghazi Mubarok (Al-Iffah: Journal of Islamic Sciences Research, 2025)
The education of aqidah and faith in the Qur'an is the main foundation in the formation of the character and morals of Muslim individuals. Aqidah includes fundamental beliefs in Allah, angels, books, apostles, the Day of Judgment, and destiny, all of which are contained in Islamic teachings. This research uses qualitative research methods. The type of research used in this research is library research (library research), namely research on literature or books or journals that are in accordance with the material being discussed. The results of research on aqidah education in the Al-Qur'an surah Al-Luqman verse 13 are Aqidah education starting from the family, advice as a method of aqidah education, prohibition of shirk as material for aqidah education. This will form a strong firm faith in the midst of the challenges of the times, not only that, the Qur'an also discusses faith education, namely in surah Al-Baqarah verse 3, namely education in faith in the unseen, then establishing prayer, and Spending some of his sustenance, faith is not only seen as a theoretical belief, but also as an encouragement to act and do good according to Allah's commands.